2022
DOI: 10.1002/dad2.12355
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese version of the CDR plus NACC FTLD: Validation studies

Abstract: Introduction The CDR Dementia Staging Instrument PLUS National Alzheimer’s Coordinating Center (CDR plus NACC FTLD) was developed by adding to the standard CDR two extra domains focused on the main features of frontotemporal lobar degeneration (FTLD): language and behavior/personality. We intended to perform the validation studies for the European‐Portuguese population. Methods A total of 105 participants matched for age, education, and disease staging (35 bvFTD, 35 AD, and 35 controls) were included. A transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…ROC curve analysis showed that the BEHAV and LANG domain of the CDR® plus NACC FTLD distinguished between patients with AD dementia and FTD better than the MEMORY domain of the CDR®. This result is consistent with those of previous studies 7,8,10 . Although the CDR® plus NACC FTLD was not developed to distinguish FTD from other types of dementia, it may be useful in distinguishing FTD from AD dementia.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…ROC curve analysis showed that the BEHAV and LANG domain of the CDR® plus NACC FTLD distinguished between patients with AD dementia and FTD better than the MEMORY domain of the CDR®. This result is consistent with those of previous studies 7,8,10 . Although the CDR® plus NACC FTLD was not developed to distinguish FTD from other types of dementia, it may be useful in distinguishing FTD from AD dementia.…”
Section: Discussionsupporting
confidence: 92%
“…This study had some limitations. First, the number of patients, particularly with PNFA, was less than that in previous studies 5–8,36 . However, 50 patients were sufficient to evaluate the inter‐ and intra‐rater reliability, validity, and responsiveness.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations